Uncontrolled Donation Potential After Circulatory Death in Slovenia Could Lead to More Organ Donations: Extrapolation of SiOHCA Study Data. - Kulovec, Domen; Petravić, Luka; Miklič, Rok; Burger, Evgenija; Keše, Urša; Poljanšek, Eva; Tomšič, Gašper; Pintarič, Tilen; Faria Lopes, Miguel; Turnšek, Ema; Gadžijev, Andrej; Strnad, Matej (Inquiry (00469580), 2024)
Out-of-hospital cardiac arrest is one of the major health challenges faced by developed countries. Donation after circulatory death is a process of retrieving organs from individuals whose death has been confirmed by circulatory or respiratory criteria. In 2018, 136 625 people were listed on the waitlist covering over 16 countries. Out of these 136 625 individuals, 7383 died whilst waiting that year. The aim of this study is to assess the potential for the uncontrolled donation after circulatory death among out-of-hospital cardiac arrest patients in Slovenia. This non-interventional study was conducted using the Slovenian out-of-hospital cardiac arrest registry dataset. The database measured Out-of-hospital cardiac arrest in Slovenia between September and November 2022. From the database we chose patients who would be identified as donors by the uncontrolled donation after circulatory death guidelines for patient selection. Using the selection criteria we have narrowed the used data set from 294 unique patient records to 19. There were no organ donors in the cohort. With extrapolation we calculated that in 2022 there could be 111 donors in Slovenia that would fit the uncontrolled donation after circulatory death criteria. This equates to 52.4 pmp/y. We conclude that uncontrolled donation after circulatory death program in Slovenia would positively impact patients. Although our study is limited by a small sample of out-of-hospital cardiac arrest patients and short duration of the Slovenian out-of-hospital cardiac arrest registry inclusion, the results offer a good foundation to further explore uncontrolled organ donation in Slovenia and similar countries.